Safety testing of acellular pertussis vaccines: Use of animals and 3Rs alternatives - Marieke Hoonakker; Juan Arciniega; Coenraad Hendriksen (Taylor & Francis Group, 2017)
The current test of acellular Bordetella pertussis (aP) vaccines for residual pertussis toxin (PTx) is the Histamine Sensitization test (HIST), based on the empirical finding that PTx sensitizes mice to histamine. Although HIST has ensured the safety of aP vaccines for years, it is criticized for the limited understanding of how it works, its technical difficulty, and for animal welfare reasons. To estimate the number of mice used worldwide for HIST, we surveyed major aP manufacturers and organizations performing, requiring, or recommending the test. The survey revealed marked regional differences in regulatory guidelines, including the number of animals used for a single test. Based on information provided by the parties surveyed, we estimated the worldwide number of mice used for testing to be 65,000 per year: ∼48,000 by manufacturers and ∼17,000 by national control laboratories, although the latter number is more affected by uncertainty, due to confidentiality policies. These animals covered the release of approximately 850 final lots and 250 in-process lots of aP vaccines yearly. Although there are several approaches for HIST refinement and reduction, we discuss why the efforts needed for validation and implementation of these interim alternatives may not be worthwhile, when there are several in vitro alternatives in various stages of development, some already fairly advanced. Upon implementation, one or more of these replacement alternatives can substantially reduce the number of animals currently used for the HIST, although careful evaluation of each alternative's mechanism and its suitable validation will be necessary in the path to implementation.